IMPLEMENTASI METODE TALAQQI DALAM MENINGKATKAN KUALITAS HAFALAN AL-QUR’AN PADA SANTRI WILAYAH AL-MAWADDAH - Aini, Indah Nur Aini; Feriska Listrianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of the talaqqi method in improving the quality of Quranic memorization among students at Pondok Pesantren Nurul Jadid, Al-Mawaddah region. The research employed a qualitative case study approach, with data collected through observation, interviews, and documentation. The findings indicate that the talaqqi method is effective in enhancing reading accuracy, improving memorization fluency, and strengthening concentration, memory, learning motivation, and self-confidence of the students. The success of implementation is influenced by the competence and dedication of the instructors, support from guardians, and a conducive pesantren environment. Inhibiting factors include limited learning time, emotional instability, and academic workload, requiring adaptive strategies. The findings confirm that the talaqqi method not only contributes to improving memorization quality but also supports cognitive, emotional, and spiritual development. This study recommends integrating the talaqqi method into the tahfizh curriculum across various levels of Islamic education for optimal outcomes